2004
DOI: 10.1080/10682760310001647044
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the location, size, orientation and shape of a rigid cylindrical body from simulated and experimental scattered acoustic field data

Abstract: The Intersecting Canonical Boundary Approximation (ICBA) [T. Scotti and A. Wirgin (1995). Shape reconstruction using diffracted waves and canonical solutions. Inverse Probs., 11, 1097; A. . Wide-band approximation of the sound field scattered by an impenetrable body of arbitrary shape. J. Sound Vibr., 194, 537.] is employed as the estimator to recover the location, size, orientation and shape of an acoustically-rigid body from both simulated data obtained from a boundary element code, and real data obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…(1)) would fail. Interestingly, two reports [41, 43] for different inverse problem solutions both confirm that additional information is needed to obtain unique solutions. In particular, Barbone and colleagues [41] analytically demonstrated that additional force boundary conditions ( e.g .…”
Section: Discussionmentioning
confidence: 97%
“…(1)) would fail. Interestingly, two reports [41, 43] for different inverse problem solutions both confirm that additional information is needed to obtain unique solutions. In particular, Barbone and colleagues [41] analytically demonstrated that additional force boundary conditions ( e.g .…”
Section: Discussionmentioning
confidence: 97%